Teaching Modern Islamic History in Southeast Asia: The Cases of Patani and Mindanao - Nurlidiawati Nurlidiawati; Rahmawati Rahmawati; Abdul Khalik; Nurhafsah Nurhafsah; Satry Ayub; Syukri Syukri (International Journal on Advanced Science, Education, and Religion, 2026)
Islam in Southeast Asia has developed through a long and complex historical trajectory, particularly in regions where Muslims currently occupy a minority position within modern nation-states. This article examines the history of modern Islam in Patani (Southern Thailand) and Mindanao (Southern Philippines) as two significant regions representing the dynamics of Muslim minority communities in Southeast Asia. This study employs a historical–qualitative approach using a literature review of contemporary historical, social, and political works. The findings indicate that modern Islam in Patani and Mindanao has been shaped not only by early Islamization processes but also significantly influenced by colonialism, state nationalist policies, educational modernization, as well as conflict and peace processes. In both regions, Islam has evolved as a religio-cultural identity that continuously negotiates with state power and global realities. This article asserts that modern Islam in Patani and Mindanao represents a form of creative adaptation by Muslim communities in maintaining their identity, dignity, and social sustainability.